PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI INTERAKSI ANTAR NEGARA ASIA DAN NEGARA LAINNYA MATA PELAJARAN IPS DI KELAS IX-J MTsN 1 KOTA KEDIRI PADA SEMESTER GANJIL TAHUN PELAJARAN 2023-2024 - Mardiah Hayati (CV. Denasya Smart Publisher, 2025)
Social Studies learning, particularly the ability to analyze interactions between Asian countries and other nations at MTsN 1 Kota Kediri, is still teacher-centered. Students are not accustomed to participating in discussions, tend to be passive, and their engagement remains low. They mostly wait for the teacher's explanation during the learning process without actively thinking. Moreover, students do not review the material at home and are often used to copying their peers' work during practice activities. The purpose of this research is to determine the improvement in students’ ability to analyze interactions between Asian countries and other nations in class IX-J of MTsN 1 Kota Kediri during the even semester of the 2023–2024 academic year by applying the Problem-Based Learning (PBL) model. This method is one of the enjoyable strategies that encourages students to be active in the learning process. The success indicator for improved student learning outcomes in this study is that more than 76% of students meet the Minimum Mastery Criteria (KKM), with a minimum score of 76. The research results show an increase in the number of students who achieved the minimum mastery criteria in each cycle. In the first cycle, 73.3% (13 students) met the KKM, while in the second cycle, 86.8% (36 students) met the KKM. These results demonstrate an improvement from the pre-cycle to the second cycle. The success criteria of the study were met in the second cycle, where more than 76% of the students achieved the KKM.